Neuropathology Education Using Social Media. Issue 6 (16th May 2018) - Nix, James S; Gardner, Jerad M; Costa, Felipe; Soares, Alexandre L; Rodriguez, Fausto J; Moore, Brian; Martinez-Lage, Maria; Ahlawat, Sunita; Gokden, Murat; Anthony, Douglas C
Abstract: Social media use continues to grow among pathologists. Discussions of current topics, posts of educational information, and images of pathological entities are commonly found and distributed on popular sites such as Facebook and Twitter. However, little is known about the presence of neuropathology content in social media and the audience for such content. We designed and distributed a survey to assess the demographics of users viewing neuropathology content and their opinions about neuropathology in social media. User posts on the Facebook group, Surgical Neuropathology, were also analyzed. The results show that there is a demand for neuropathology content of high quality, curated by experts, and that this demand is present among both specialists and nonspecialists. These findings suggest that social media may be useful for rapid dissemination of information in the field of neuropathology. This format also offers a unique opportunity to extend the reach of information to nonneuropathologists who may not receive neuropathology journals or have access to specialty-level neuropathology training, to build networks between professionals, and potentially to influence public opinion of neuropathology on an international scale.